Blockade of hedgehog pathway is required for the protective effects of magnesium isoglycyrrhizinate against ethanol‐induced hepatocyte steatosis and apoptosis. Issue 7 (12th May 2017) - Lu, Chunfeng; Xu, Wenxuan; Shao, Jiangjuan; Zhang, Feng; Chen, Anping; Zheng, Shizhong
Abstract: Alcoholic liver disease (ALD), characterized by excessive deposition of lipids in hepatocytes, causes heavy health burden personally and socially. Mechanistically, hedgehog signaling was activated during the development of ALD, and exerted compelling role in regulating lipometabolism. The current promising intervention strategy is inhibition of lipid accumulation and apoptosis in hepatocytes. Magnesium isoglycyrrhizinate (MgIG) has been widely used in various liver diseases for its good hepatoprotective activities. However, the role of MgIG in ALD has not been elucidated. Therefore, this study was aimed to explore the role of MgIG and further identify the potential mechanisms. We found for the first time that MgIG reduced lipid accumulation, including triglyceride, and total cholesterol, probably via inducing peroxisome proliferator‐activated receptor‐alpha and inhibiting sterol regulatory element‐binding protein‐1c. Further, MgIG alleviated ethanol‐induced oxidative stress, evidenced by reduced abundance of reactive oxygen species and increased levels of glutathione, superoxide dismutase, and mitochondrial transmembrane potential. Besides, MgIG protected hepatocytes from ethanol‐induced apoptosis. In addition, MgIG dose‐dependently suppressed hedgehog signaling. Of note was that disruption of hedgehog signaling could mimic the effects of MgIG, whereas activation of hedgehog signaling abrogated the effects of MgIG. These findings suggested that MgIG prevented ethanol‐induced hepatocyte steatosis and apoptosis via a hedgehog signaling inhibition‐dependent mechanism. © 2017 IUBMB Life, 69(7):540–552, 2017